(untitled) (Journal of Engineering, 2009)
One of the major problems facing the industrial utilities especially cooling towers is biofouling. Many techniques and measures have been taken and still continuing researches are under way. Biocides and water qualities were the main area of research for evaluation. Friendly biocides are preferable for controlling viable count and fungi, but many harmful still in use. The main objective of this research work is to predict a relationship covering the concentration of Cl and Br – containing compounds as biocide and the performance. It was concluded that the chlorophenol is the major effective biocide used (reduce it for about 80%, while bromophenol to about 65%) and that material although they are highly approved, but suffer pitting corrosion.